Simulating Primary Manufacturing Area (PMA) activities of fixed trailing edge panels production - Mohd Nawawi, Mohd Kamal; Mat Tahar, Razman (Universiti Utara Malaysia, 2004)
Simulation clearly has the potential to play an important role in manufacturing decision-making at many levels. This simulation study is conducted at the local manufacturing plant that manufactures fixed trailing edge panels for the aerospace industry. The model focused on operational activities at the primary manufacturing area of cutting and laminating of aircraft’s composite parts. The model built was used to investigate a variety of issues, for example to determine the impact of a proposed change, without affecting production.The result shows that when production rate was increased by 20% to investigate the current plant capacity, the current resources capacity was unable to tolerate this increment. From the model experimentation, an increase of 60 minutes working time for ply cutter machines and 75 minutes of lay up operators found to be the best design to meet the expected production throughput and increase resources utilisation.